12(m-4)=3m-3

Simple and best practice solution for 12(m-4)=3m-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(m-4)=3m-3 equation:


Simplifying
12(m + -4) = 3m + -3

Reorder the terms:
12(-4 + m) = 3m + -3
(-4 * 12 + m * 12) = 3m + -3
(-48 + 12m) = 3m + -3

Reorder the terms:
-48 + 12m = -3 + 3m

Solving
-48 + 12m = -3 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
-48 + 12m + -3m = -3 + 3m + -3m

Combine like terms: 12m + -3m = 9m
-48 + 9m = -3 + 3m + -3m

Combine like terms: 3m + -3m = 0
-48 + 9m = -3 + 0
-48 + 9m = -3

Add '48' to each side of the equation.
-48 + 48 + 9m = -3 + 48

Combine like terms: -48 + 48 = 0
0 + 9m = -3 + 48
9m = -3 + 48

Combine like terms: -3 + 48 = 45
9m = 45

Divide each side by '9'.
m = 5

Simplifying
m = 5

See similar equations:

| 1/2d=7 | | 8x-6y=6 | | 9w+3=7g+4 | | -12=-2x+2(22-6x) | | 3x+14y=203 | | n/2.8-4.9=-7.11 | | x-12x+5=-50 | | 4-3/2 | | 2x+5=9x-16 | | d=c-13p | | 45=16+x | | -4(3x+1)+5=13 | | 16x+7=-73 | | (5p+3)(5p+3)=8 | | 16x=-73 | | -64x=-1280 | | -7x-3(5x+12)=-146 | | -64x=1280 | | 7+x-(3+32/8)=3 | | X/18=X/960 | | 5(y-3)=8(y-6) | | 2/3=4/5m | | 5t-5=7+2a | | 36=1y+5y+12 | | 14u+4u-15u-2u=8 | | 6(6x+6)-5=1+6v | | -21/(x^2+3) | | 8w-2(2+w)=25 | | -7x-6(-2x+10)=-115 | | 5(2+5x)=-28+6x | | 114=10.5x+30 | | y/-15-112=-88 |

Equations solver categories